Bacteria Associated with Granulomatous Lobular Mastitis and the Potential for Personalized Therapy. Issue 1 (2nd January 2022) - Li, Xin-Qian; Wu, Hong-Li; Yuan, Jing-Ping; Liu, Tian-gang; Sun, Sheng-Rong; Chen, Chuang
Abstract: Granulomatous lobular mastitis (GLM), also known as idiopathic granulomatous mastitis (IGM), is a chronic inflammatory lesion of the breast. The incidence of GLM has been increasing in recent years, especially among young women. The etiologies of GLM have not been fully elucidated but are associated with autoimmunity and bacterial infection. Bacteria, especially Corynebacterium species, play important roles in GLM. In this article, we review research progress regarding the bacteriology of GLM attained with the application of several new high-throughput detection techniques. Accurate detection might be important for deepening our understanding of the pathogenesis of GLM and hold promise for personalized GLM therapy.